5 - Book Reviews: The IMF and World Bank in Africa : Conditionality, Impact and Alterna- tives - Edited by Kjell J. Havnevik (Uppsala, Scandinavian Institute of Afri- can Studies, 1987) 186 pp. SEK 110).: by Akwasi Aidoo - Akwasi Aidoo (Africa Development, 1989)
abstract